The significance of the utterance of the tools according to Al-Samin Al-Halabi (may God have mercy on him) in his book Umdat Al-Hafaz fi Tafsir Ashraf Al-Alfaz (d. - Khalaf , Bashir; Ali , Osman (Islamic Sciences Journal, 2023)
ABSTRACT Praise be to Allah, Lord of the Worlds, and prayers and peace be upon the Master of the Messengers, and upon his family and companions altogether. This book is considered a source for linguists and interpreters at the same time, so the student of language vocabulary finds what he needs in it, as it meets a detailed analysis of the words of the Qur’an, their origins, derivations, development and uses, as well as the interpreter can use it in his interpretation, and this is the most important advantage of this book. Among its advantages also: the author begins his book with an accurate index of the materials that he dealt with in his book, and this indicates its accuracy, good classification and organization, and also its richness in strange hadiths, Arabic evidence, and Arabic grammar research. With the linguistic truth of Al-Samin Al-Halabi (may Allah have mercy on him) in his book, which is: (pots - cups - paper), and these terms were stated by Al-Samin Al-Halabi (may Allah have mercy on him) in his book, and I took a share of the study in this research.